Susceptibility‐guided therapy for Helicobacter pylori‐infected penicillin‐allergic patients: A prospective clinical trial of first‐line and rescue therapies. Issue 4 (19th May 2020) - Luo, Laisheng; Huang, Yu; Liang, Xiao; Ji, Yingjie; Yu, Lou; Lu, Hong
Abstract: Background: Helicobacter pylori ( H pylori ) treatment remains a challenge for penicillin‐allergic patients. Aim: To evaluate the efficacy and tolerability of susceptibility‐guided first‐line and rescue treatment in H pylori ‐infected penicillin‐allergic patients. Methods: Consecutive H pylori ‐infected patients with penicillin allergy received a 14‐day triple or quadruple therapy based on susceptibility to clarithromycin, levofloxacin, and metronidazole. All received esomeprazole 20 mg twice a day. Metronidazole‐susceptible infections received metronidazole plus clarithromycin or levofloxacin triple therapy if susceptible. Clarithromycin‐ and levofloxacin‐resistant infections received metronidazole plus tetracycline triple therapy. Metronidazole‐resistant infections received a bismuth—high‐dose metronidazole plus clarithromycin or levofloxacin quadruple therapy. Triple‐resistant infections received classical bismuth quadruple therapy with high‐dose metronidazole. Antimicrobial susceptibility was assessed using the E test method. Results: 112 patients were entered (34.8% men, average 47.1 years). Infections in 83.8% (31/37) of treatment‐naive subjects and 12.0% (9/75) ( P < .001) receiving rescue treatment were susceptible to at least one of the three tested antibiotics. Overall, susceptibility‐guided therapy achieved eradication rates of 92.9% (104/112, 95% CI 88.1%‐97.7%) by intent‐to‐treat analysis and 99% (100/101, 95% CI 97.1%‐100%) by per‐protocol analysis. All regimens achieved eradication rates greater than 90% ( P = .327) in the PP populations. Adverse events were relatively frequent; however, compliance remained high. Conclusion: Susceptibility‐guided therapy proved highly effective for penicillin‐allergic patients. When available and proven locally effective, the alternative was empiric classical bismuth quadruple therapy. This trial is registered with ClinicalTrials.gov as NCT03708848.